2019
DOI: 10.1038/s41598-019-55841-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Grafting, Salinity and Irrigation Water Composition on Eggplant Fruit Yield and Ion Relations

Abstract: Scarcity of fresh water in arid and semi-arid regions means that we must use more saline waters for irrigation and develop tools to improve crop salt tolerance. The objectives of our study were to (1) Evaluate fruit production, salt tolerance and ion composition of eggplant cv Angela, both nongrafted and when grafted on tomato cv Maxifort rootstock and (2) Evaluate eggplant specific toxicity effect of Cl− and Na+ ions under saline conditions. We salinized the irrigation water with either a Na+-Ca2+- Cl− compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
(60 reference statements)
1
18
0
Order By: Relevance
“…Food quality can be influenced by salinity in both glycophytic crops (e.g., Lactuca sativa, Eggplant, Cucumis sativus, and Solanum lycopersicum) as well as in halophytes (e.g., Crithmum maritimum and Salicornia persica) [29,[44][45][46][47]. Chlorophylls and Carotenoids are nutritionally valuable compounds that are associated with health-promoting effects and are particularly abundant in green leafy vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Food quality can be influenced by salinity in both glycophytic crops (e.g., Lactuca sativa, Eggplant, Cucumis sativus, and Solanum lycopersicum) as well as in halophytes (e.g., Crithmum maritimum and Salicornia persica) [29,[44][45][46][47]. Chlorophylls and Carotenoids are nutritionally valuable compounds that are associated with health-promoting effects and are particularly abundant in green leafy vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that the ability of a plant to manage Na, Cl, and K during salinity stress is critical for its ability to tolerate salinity 24,25,40 . After evaluating these cultivars under the hot eld climatic conditions of southern California for their whole cycle, it is reasonable to assume that, for the cultivars reported here as salt-sensitive, salt effects were related to ion toxicity rather than osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, in both tomato 24 and eggplant 25 , there was no signi cant difference in yield between salt solutions dominant in Cl − or SO 4 − , suggesting that Na + is the dominant toxic ion for these species. This conclusion was con rmed by predicting eggplant yield of two different salt-tolerant cultivars, based on leaf Na concentration, but not with leaf Cl concentration 25 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Local varieties have genotypes that adapt easily to the growing environment, such that they are easier to cultivate than varieties originating from other regions [20,21]. e grafting combination can determine plant resistance, expressed through variation in growth, fruit yield and production quality [22][23][24][25][26][27]. A previous study comparing self-grafted plants and controls reported only four statistically significant differences out of a total of 53 cases and concluded that the inclusion of self-grafted treatments is unnecessary [28].…”
Section: Introductionmentioning
confidence: 99%